Mobile multicast in wireless mesh networks - Sanni, Mistura L.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Naji, Ahmed Wathik; Ahmed, Gharib Subhi Mahmoud (INSI Publications, 2011)
There is increased deployment of portable IP-enabled devices and group content distribution applications on Wireless Mesh Networks (WMNs). This surge is facilitated by its relative low cost of installation and as such is an attractive option in environments lacking existing communication infrastructure and/or in times of natural emergencies. The WMNs is equally capable of providing high bandwidth “multihop” access to the web. The capability of the WMNs can be enhanced by reinforcing the system with multicasting and mobility features. However, there are challenges of seamless integration when such existing multicasting and mobility features of MANET and fixed networks are migrated to the WMNs domain. Thus, a wide range of efforts have been directed at finding solutions to these challenges in order to increase the widespread deployment of the WMNs based communication infrastructure. This paper provides an exploratory review of reported studies in the sphere of multicast routing, mobility management and their integration in WMNs. It also highlights emerging issues in WMNs performance that deserves research attention or focus particularly in the area of integrated mobile multicasting. This is done with a view to producing a one volume comprehensive account of incorporating multicasting with mobility support deployable via Wireless Mesh Networks. In addition, this work is aimed at propelling research directions in the area of integrated mobile multicasting on Wireless Mesh Networks.